ANALISIS PENGELOLAAN STOK OBAT BERDASARKAN PERSENTASE WAKTU KEKOSONGAN DAN NILAI OBAT KADALUARSA DI PUSKESMAS X - Maya Nurul Paidah; Tisa Amalia; Ayu Izzatin Haifa (INKOFAR, 2025)
Effective drug stock management is crucial for ensuring medication availability and minimizing financial losses due to expired drugs in primary healthcare facilities. This study aimed to analyze drug stock management based on the percentage of stockout time and the value of expired drugs at Public Health Center (Puskesmas) X. This descriptiveanalytical research employed a mixed-method approach conducted from January to December 2024. Data were collected through observation, interviews, and document review. Quantitative data were analyzed using formulas for stockout percentage and expired drug percentage, while qualitative data were analyzed thematically. The results showed a stockout percentage of 23.87%, with 47 out of 94 indicator drugs experiencing stockouts. The expired drug percentage was 2.12%, with a total financial loss of IDR 2,693,966. The main causes were ineffective distribution, changing disease trends, and inaccurate planning. In conclusion, drug management at Puskesmas X is not yet optimal, as indicated by high rates of stockouts and expired drugs. Improvements in planning, distribution, and monitoring are required.